Peran Seni Visual Terhadap Komunitas Musik Underground ISBI Bandung - Sagara Mata Dewa; Agus Cahyana; Asep Miftahul Falah; Martien Roos Nagara (Jurusan Seni Rupa ISBI Bandung, 2025)
This research aims to understand the role of visual art in shaping identity, strengthening communication, and supporting the existence of a new generation of underground music communities in Bandung, with a focus on communities within the ISBI Bandung environment. The study highlights how visual elements such as posters, logos, album covers, and merchandise designs function as mediums of expression, promotion, and representation of the community’s collective values-including the spirit of inclusivity, resistance, and D.I.Y. (Do It Yourself). The research employs a qualitative analytical approach, using data collection techniques such as interviews, participatory observation, and documentation study. Data were gathered from community members and visual artists directly involved in the ISBI Bandung ecosystem. The findings show that collaboration between musicians and visual artists occurs organically, based on friendships, yet maintains a level of professionalism. Visual art plays a crucial role in reinforcing the musical message and expanding the community’s reach into digital spaces, particularly through social media platforms like Instagram. Beyond its aesthetic function, visual art serves as an effective communication tool that bridges artistic and social experiences between the community and the public. This research affirms that visual art is a fundamental element in shaping an alternative cultural ecosystem amid the currents of globalization and the dominance of popular culture.